A computational approach to the characterization of a microfluidic device for continuous size-based inertial sorting. (31st May 2017) - Volpe, A; Paiè, P; Ancona, A; Osellame, R; Lugarà, P M; Pascazio, G
Abstract: The application of fully-inertial size-based microfluidic filtration technologies for particle separation is an attractive tool, which not only offers label-free control of the microenvironment during separation, but also facilitates integration and automation for high throughput sample processing. In this work, we exploit 3D computational fluid dynamics (CFD) simulations based on the lattice Boltzmann method to evaluate the performance of a microfluidic device specifically designed to trap and extract particles by inertial focusing and microscale vortices. The device geometry consists of a straight microchannel, followed downstream by a microchamber with outlets for continuous size-based separation. Simulations were carried out to characterize the flow properties of the microfluidic device. Here, the influence of the Reynolds number (Re), the chamber dimensions and the outlet channels aspect ratio on the streamtracer distribution were studied. In order to support the simulation results, some preliminary experimental validations have been conducted, finding that the model can accurately characterize the flow in the studied geometry. The results of the simulations and experiments presented in this paper can be very useful to support the design of continuous-flow particle sorting lab-on-a-chip (LOC) devices.